PENGUATAN KAPASITAS PEREMPUAN SEBAGAI STEAKHOLDER DALAM PENANGGULANGAN KORBAN BENCANA BANJIR DI PANGKALAN - Suyito Suyito; Redni Putri Meldianto; Siti Annisa; Tesi Prima (HUMANISMA : Journal of Gender Studies, 2019)
This article examines the fulfillment of women's rights in disaster situations that occur in Pangkalan Koto Baru District. The flood disasters occurred in the study area had an impact on women and men, especially when in refugee camps when the disaster occurred. Stakeholders as the ones who is responsible for handling problems in this refugee camp should be professional person in handling people based on gender and age. This has become very important act because women are included in vulnerable groups and require special treatment on emergency. It turns out that women are more vulnerable groups as victims of disasters than men. Based on these conditions, women need variety of strengths dealing with disasters, in order to rise from the threats as the impact of the disaster. The strengthening capacity of women was related to the strengthening of economic, psychological, and mentality. It was done to fulfill the women's rights when disasters happen and its impacts.